Dual‐Loop Antennas With a Branched Feed‐Line for Broadband Circular Polarisation - Hirose, Kazuhide; Mita, Shintaro; Urushibata, Yuya; Nakano, Hisamatsu (Electronics letters, 2025)
Using the method of moments, we first analyse reference and present dual‐loop antennas with a perturbation segment and branched feedline, respectively. The loop elements of each antenna are gradually rotated for an increased 3 dB axial ratio bandwidth. Analysis reveals that as the loop rotation angle increases, the bandwidths of the reference and present antennas reach 20% and 43%, respectively, twice and three times as broad as those of the corresponding antennas without the rotation. Next, we modify the present antenna using a sequential rotation technique and discuss the radiation characteristics. The simulated results are verified with experimental ones.